Preliminary studies on the eff ect of bioactive substances of Hypnea musciformis (Wulf.) Lamour. on the growth of seedlings in green gram, Vigna radiata L. - Nil Gopalakrishnan, Chitra; T, Binumol (Journal of Phytology, 2016)
The effect of seaweed liquid fertilizer (SLF) of Hypnea musciformis (wulf.) Lamour.was tested at different concentrations (1, 2, 3 and 4 g/ml) on seed germination and biochemical constituents of Vigna radiata L. The extracts promoted seed germination at lower levels of SLF application. The seeds treated with, 2 g/ ml concentration showed maximum seed germination, radicle length, hypocotyl length, seedling length, fresh weight, phytomass, productivity, phytotoxicity, and photosynthetic pigments like Chlorophyll A, B, and total chlorophyll. Moreover, the different extracts of seaweed were subjected to phytochemical screening. All the tested compounds (tannins, alkaloids, saponins, glycosides, and steroids) were present in varied degrees in Hypnea. The result of the present study can help in the identification and selection of raw materials in agriculture and drug industry.